Circling the square: Governance of the circular economy transition in the Amsterdam Metropolitan Area - Heurkens, Erwin; Dąbrowski, Marcin (European Spatial Research and Policy, 2020)
Circular economy (CE), the new ‘buzzword’ in urban and regional studies and policy debates, is about shifting from a linear production process towards a circular one in which the generation of waste is minimised, materials circulate in ‘closed loops’, and waste is not considered a burden but rather a resource that brings new economic opportunities. However, while there is a consensus on the need to facilitate a transition towards a circular economy, the governing of this endeavour remains extremely challenging because making a circular economy work requires cutting across sectoral, scalar, and administrative boundaries. Drawing on the sustainability transitions literature and the case of the Amsterdam Metropolitan Area, arguably one of the frontrunners on the strive towards a circular built environment and economy, the paper seeks to identify and understand barriers for CE transition at a regional scale. The findings underscore the multi-faceted nature of the challenge and offer lessons for the governance of emerging regional circular spatial-economic policies.